2021
DOI: 10.1088/1748-0221/16/10/c10008
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional visualization of a beta-emitting nuclide by combining a directional Geiger-Mueller counter and structure from motion

Abstract: At the Fukushima Daiichi Nuclear Power Station (FDNPS) where an accident occurred due to a large tsunami caused by the Great East Japan Earthquake, understanding the distribution of radioactive substances is important to reduce the exposure dose to workers and establish decontamination plans. We focused on the importance of visualizing beta-emitting radiation sources in addition to gamma-emitting ones and proposed a method for three-dimensionally (3D) visualizing the location of beta-emitting radiation sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Our network was trained for both photons and neutrons and is able to provide a location estimation for either type of source in real-time. Other studies showed the MR visualization of radiation hot spots on a tablet device or AR using data from Geiger Mueller counters on a robot 30 or a UAV 31 . We build upon these by demonstrating MR visualization in real-time, on a head mounted device, for both gamma ray and neutron detection.…”
Section: Discussionmentioning
confidence: 99%
“…Our network was trained for both photons and neutrons and is able to provide a location estimation for either type of source in real-time. Other studies showed the MR visualization of radiation hot spots on a tablet device or AR using data from Geiger Mueller counters on a robot 30 or a UAV 31 . We build upon these by demonstrating MR visualization in real-time, on a head mounted device, for both gamma ray and neutron detection.…”
Section: Discussionmentioning
confidence: 99%
“…In such case, the sample is repeatedly counted for the in-growth of 90 Y; thereby, the activity of 90 Sr can be calculated. Sato et al [115] have developed a technique to visualize the locations of 90 Sr source in 3D by combining a directional GM counters with Structure from Motion (SfM) and a method to estimate the radioactivity of the visualized source. Additionally, by combining a beta-ray detector with a Compton camera, they demonstrated that 90 Sr and 137 Cs can be visualized separately.…”
Section: Beta Countermentioning
confidence: 99%